2019
DOI: 10.1038/s41598-019-42952-x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobiosis influences virulence properties of Pseudomonas aeruginosa cystic fibrosis isolates and the interaction with Staphylococcus aureus

Abstract: The airways of individuals with cystic fibrosis (CF) are abundantly colonised by Staphylococcus aureus and Pseudomonas aeruginosa . Co-infecting hypoxic regions of static mucus within CF airways, together with decreases in pulmonary function, mucus plugging and oxygen consumption by host neutrophils gives rise to regions of anoxia. This study determined the impact of anaerobiosis upon S. aureus - P. aeruginosa interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 99 publications
1
43
0
Order By: Relevance
“…Also, longitudinal clinical studies would be appropriate to analyze the kinetics of interaction evolution over time and determine how it could affect patients’ health. Furthermore, the conditions and environmental factors leading to co-existence instead of competition require clarification, particularly through studies such one conducted recently that demonstrated the positive impact of hypoxia found in static mucus within CF airways on a coexisting interaction 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, longitudinal clinical studies would be appropriate to analyze the kinetics of interaction evolution over time and determine how it could affect patients’ health. Furthermore, the conditions and environmental factors leading to co-existence instead of competition require clarification, particularly through studies such one conducted recently that demonstrated the positive impact of hypoxia found in static mucus within CF airways on a coexisting interaction 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this state of coexistence is apparently solely attributable to P. aeruginosa , the selective advantage for P. aeruginosa leads to questions. Indeed, previous studies showed that cocultivation with S. aureus induces LPS mutation in P. aeruginosa associated with fitness gain and antibiotic resistance 41 , and that S. aureus exoproducts restore and enhance P. aeruginosa motility 32 . The state of coexistence could thus represent a trade-off allowing both pathogens to benefit mutually and maintain equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Since this state of coexistence is apparently solely attributable to P. aeruginosa , the selective advantage for P. aeruginosa leads to questions. Indeed, previous studies showed that cocultivation with S. aureus induces LPS mutation in P. aeruginosa associated with fitness gain and antibiotic resistance 41 , and that S. aureus exoproducts restore and enhance P. aeruginosa motility 32 . The state of coexistence could thus represent a trade-off allowing both pathogens to benefit mutually and maintain equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…In CF patients, during the adolescence and early adulthood, P. aeruginosa replaces S. aureus but sometimes this latter is still detected in CF adults. Pallet et al studied the co-infection of CF airways by S. aureus and P. aeruginosa under normoxia and anoxia [113]. Amongst three CF isolates, one presented no anti-staphylococcal activity.…”
Section: Proteomics For Host-pathogen Studiesmentioning
confidence: 99%